Murder on amsterdam avenue eaudiobook - Thompson, Victoria (Gaslight Mystery, 2015)
In this Gaslight Mystery from the national bestselling author of Murder in Murray Hill, midwife Sarah Brandt and Detective Sergeant Frank Malloy investigate foul play in the secretive high-society world of nineteenth-century New York City. In the midst of Sarah and Frank's wedding preparations, Sarah accompanies her mother on a condolence call to the Upper West Side, where Charles Fairfax, the son of family friends, has died unexpectedly after suffering from a mysterious disease. It is a tragic and all too common story-or so it seems. Charles's father asks to speak with Sarah privately. He believes his son was poisoned and would like Sarah and Frank to look into the matter with the utmost discretion. Putting their own personal affairs on hold, Sarah and Frank soon learn that not everyone wants to know more about Charles's death, particularly if he was murdered. As they unravel secrets that reach back to the War Between the States, they also discover that they are in the company of a very present danger.